Strategi Pengembangan Sumber Daya Manusia Untuk Meningkatkan Kinerja Aparatur Di Sekretariat DPRD Kota Pekanbaru - Asri Karly; Rizky Setiawan (Journal of Research and Development on Public Policy, 2024)
The research results found that the DPRD Secretariat's strength factors include the availability of skilled personnel resources, the existence of measurable work programs and work mechanisms, and the existence of operational standards for providing services. Weaknesses include a lack of understanding of the implementation of the laws and regulations used, a lack of adequate facilities and infrastructure to support the implementation of duties and functions, the availability of skilled human resources in accordance with their field of work, limited budget for improving services to the DPRD. The opportunity for the Pekanbaru City DPRD Secretariat is a commitment to increasing the capacity of regional people's representative institutions to carry out their duties and functions, providing adequate facilities and infrastructure to support the implementation of their duties, providing skilled human resources in accordance with their field of duties. The threats that arise are the fulfillment of the DPRD members' obligations which is not yet optimal, the interaction between the DPRD and the Pekanbaru City DPRD Secretariat which can affect professionalism as an apparatus, mobility and workload which is quite high, the limited number of qualified and competent employees, the availability of facilities and infrastructure which is still lacking.